2007
DOI: 10.1677/erc-06-0038
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of von Hippel–Lindau syndrome and multiple endocrine neoplasia type 2 pheochromocytomas reveals different expression of chromogranin B

Abstract: Pheochromocytomas are catecholamine-producing tumors that can occur in the context of von Hippel-Lindau syndrome (VHL) and multiple endocrine neoplasia type 2 (MEN2). Pheochromocytomas in these two syndromes differ in histopathological features, catecholamine metabolism, and clinical phenotype. To further investigate the nature of these differences, we compared the global protein expressions of 8 MEN2A-associated pheochromocytomas with 11 VHL-associated pheochromocytomas by two-dimensional gel electrophoresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
3
2
0
1
Order By: Relevance
“…Furthermore, we show that relative to increases in plasma catecholamines, patients with phaeochromocytomas associated with MEN 2 have higher plasma concentrations of CGA than patients with VHL syndrome. These fi ndings extend previous observations of other conspicuous differences, ranging from the clinical presentation of patients and catecholamine biochemical profi les of tumours [14,19] , to the expression of key chromaffi n cell markers including monoamine transporters, neuropeptide Y, and chromogranin B [15,20,21] . Previous studies have established that phaeochromocytomas from VHL patients contain fewer secretory granules than MEN 2 tumours [14,15] .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, we show that relative to increases in plasma catecholamines, patients with phaeochromocytomas associated with MEN 2 have higher plasma concentrations of CGA than patients with VHL syndrome. These fi ndings extend previous observations of other conspicuous differences, ranging from the clinical presentation of patients and catecholamine biochemical profi les of tumours [14,19] , to the expression of key chromaffi n cell markers including monoamine transporters, neuropeptide Y, and chromogranin B [15,20,21] . Previous studies have established that phaeochromocytomas from VHL patients contain fewer secretory granules than MEN 2 tumours [14,15] .…”
Section: Discussionsupporting
confidence: 87%
“…This and differences in secretory activity between VHL and MEN 2 tumours [14,15,21] represent limiting factors to use of CGA, either in tumour tissue or plasma, as a marker for distinguishing VHL from MEN 2 phaeochromocytomas. Given the differences in tumour CGA levels between MEN 2 and VHL samples in this study, together with even larger differences in chromogranin B expression observed elsewhere [20] , we hypothesize that VHL tumours possess defi ciencies in the mechanisms governing the regulated pathway of secretory vesicle formation and the storage and release of granular contents. Interestingly CGA knockout mice have increased plasma concentrations of catecholamines and neuropeptide Y but decreased adrenal catecholamine and neuropeptide Y contents compared to wildtype animals [23] .…”
Section: Discussionmentioning
confidence: 56%
“…The enzyme was also identified by proteomics analysis to show a 300-fold higher expression in MEN 2 than in VHL tumors, a result consistent with a previous study (21). The smaller differences in expression at the protein level, but still significant differences by at least one of the two microarray analyses, for tyrosine hydroxylase, the sodium-dependent norepinephrine transporter, and chromogranin A and B are also in agreement with previously published data showing higher expression of these components in MEN 2 than in VHL tumors (7,14,21,25). The smaller differences in expression at the protein level, but still significant differences by at least one of the two microarray analyses, for tyrosine hydroxylase, the sodium-dependent norepinephrine transporter, and chromogranin A and B are also in agreement with previously published data showing higher expression of these components in MEN 2 than in VHL tumors (7,14,21,25).…”
Section: Expression Of Secretory Pathway Componentssupporting
confidence: 92%
“…This combination of a germline mutation in the VHL gene and the somatic inactivation of the wildtype VHL allele in the tumor is consistent with the two-hit model of tumorigenesis. Both VHL germline missense mutations found in this study are considered to be pathogenic because these mutations have been previously reported also in other VHL families (19,20). Interestingly, Hes et al (14) described a family with a VHL p.Arg64Pro germline mutation presenting with clear cell renal cell carcinomas and pheochromocytomas and one family member with a parasympathetic paraganglioma.…”
Section: Discussionsupporting
confidence: 62%